REVIEW ARTIKEL: SOLID LIPID NANOPARTICLES (SLN) METODE DAN KARAKTERISTIK - Ilhanni Khoerunisa; Aji Najihudin; Siti Hindun (Jurnal Insan Farmasi Indonesia, 2020)
Solid Lipid Nanoparticles are composed of active substances, solid fats, water and surfactants. SLN has advantages by having a small particle size of 50-1000 nm and a large absorption efficiency value of 40-100%. SLN has a homogeneous particle size with a IP value that is closed to zero. One of the methods used to produce SLN is HSH/ High pressure homogeneity where the process uses pressure to produce small particle size. The HSH/ High-speed homogeneity method uses stirring speed as a parameter in the manufacture of nanoparticles. Solvent emulsification method does not use high temperatures in the homogeneity process. The most important SLN characteristics are particle size and entrapment efficiency values. These characteristics are strongly influenced by large concentration of solid fat and surfactants. The greater amount of the surfactant used, the smaller the particle size and the increasing value of the trap efficiency. If the solid fat concentration used is greater, the particle size will be as larger, but the absorption efficiency value will be greater because the fat will provide more space for the active substance to be entrapped.